PENGARUH KESEHATAN DAN KESELAMATAN KERJA PADA KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL - Indrawati, Ayu Desi; Satrya, I Gusti Bagus Honor; Dewi, Sayu Ketut Sutrisna (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 11 Nomor 2 Tahun 2017DO - 10.24843/MATRIK:JMBK.2017.v11.i02.p01, 2017)
Organizational commitment is an important construct in management, especially in organizational behaviour subject. This is caused organizations face many challenges such as restructuring, downsizing, re-engineering, and economic global competition, so that organizations need commitment of their member. The purpose of this research is to analyze the effect of health and safety management implementation on job satisfaction and organizational commitment.This research used sanitation officer of Dinas Kebersihan dan Pertamanan Kota Denpasar as research respondent. Data collection method used interview and quitionare and for data analysis will be used path analysis. The results showed that the implementation of health and safety management has a significant positive effect on job satisfaction and organizational commitment, and job satisfaction also has a significant positive effect on organizational commitment, and job satisfaction serve as a variable that mediates the effect of health and saftey management implementation on organizational commitment.
Keywords: kesehatan dan keselamatan kerja, kepuasan kerja, komitmen organisasional